Selective catalytic hydrogenation of biomass derived furans to secondary alcohols using Pt/polyoxometalate catalysts under mild reaction conditions - Sherbi, Magdy; Stuckart, Maria; Albert, Jakob (Biofuels Bioproducts & Biorefining-Biofpr, 2021)
Promising bifunctional catalyst systems composed of platinum and polyoxometalates (POMs) were applied successfully for the selective catalytic hydrogenation of 2,5-dimethylfuran (DMF) to 2-hexanol under mild conditions. Pt(acac)2 was found to be the most active Pt precursor for the ring opening of DMF, and the Keggin-type POM K3[PW12O40] was identified as the most promoting acidic support for 2-hexanol formation at 80 °C and 10 bar H2 pressure using n-decane as a carrier liquid. It was revealed that modifications in the synthetic procedure of the Pt/K3[PW12O40] catalytic system allowed its catalytic performance to be enhanced. Thus, a higher yield of 2-hexanol (72.5%) was achieved compared to that (49%) obtained using a commercial Pt/C catalyst with the same Pt loading. The Wells–Dawson-type POM containing catalyst Pt/K6[α-P2W18O62] was found to be selective for 2-hexanon formation (56.4% yield) under identical reaction conditions. Furthermore, furan and 2-methylfuran were also selectively hydrogenated to 1-butanol (59.7% yield) and 1/2-pentanol (44.3% yield), respectively, under the applied reaction conditions. Moreover, using analytical tools like N2-physisorption, NH3-TPD, inductively coupled plasma optical emission spectroscopy (ICP-OES), CO chemisorption, and transmission electron microscopy (TEM), revealed that the higher total acid site density of the K3[PW12O40] enhances C=O hydrogenation and overcomes the rate-limiting step of 2-hexanone hydrogenation to 2-hexanol. This demonstrates the high performance of the bi-functional catalyst system Pt/K3[PW12O40] towards ring opening of various furans and the very high selectivity towards alcohol formation. This approach opens new interesting valorization pathways for several furanic compounds with respect to sustainable alcohol formation. © 2021 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd.
CRIS-Team Scopus Importer:2021-06-11
Keywords: 2; 5-dimethylfuran; 2-hexanol; alcohol formation; polyoxometalates; ring opening; selective catalytic hydrogenation